Retrospective analysis of the effects of a highly standardized mixture of Berberis aristata, Silybum marianum, and monacolins K and KA in diabetic patients with dyslipidemia - Di Pierro, Francesco; Putignano, Pietro; Villanova, Nicola (Acta Biomedica Atenei Parmensis, 2018)
Background: Berberine, an alkaloid with both glucose- and cholesterol-lowering action, is also characterized by an anti-diarrheal effect. Consequently, berberine-based therapies are recommended for diabetic patients with irritable bowel syndrome (IBS) or gut discomfort caused by metformin. Aim: As the anti-glycemic and cholesterol-lowering action of berberine is improved by co-administration with P-glycoprotein inhibitors and naturally derived statins, we have analyzed the effect of the food supplement Berberol®K (hereafter referred to as BSM) containing, berberine, silymarin, and a highly standardized red yeast rice containing monacolins K and KA in the ratio 1:1 but no secondary monacolins, dehydromonacolins, or citrinin (Monakopure™-K20). Methods: We retrospectively evaluated the effects of BSM in 59 diabetic patients with dyslipidemia and compared the results to those obtained in patients without treatment. Enrolled subjects had a diagnosis of IBS (and diarrhea), had diarrhea caused by metformin, or were statin intolerant. Results: After 6 months of BSM treatment, significant reductions of approximately 5%, 23%, 31%, and 20% were observed in glycated hemoglobin (HbA1c), total cholesterol (TC), low density lipoprotein-cholesterol (LDL), and triglyceride (TG) levels, respectively, and only five of the 31 treated subjects reported diarrhea compared with 22 of the 28 untreated patients. Regarding safety, treatment with BSM did not significant modify creatine phosphokinase (CPK), creatine, aspartate aminotransferase (AST) or alanine aminotransferase (ALT). Conclusion: BSM is a safe and effective food supplement likely useful as add-on therapy in diabetic subjects with dyslipidemia, especially if they are statin intolerant or with diarrhea caused by IBS or metformin.